An investigation of chiral diamides as organocatalysts in asymmetric aldol reaction - Yilmaz, Dilek Gul; Aydogan, Feray; Yolacan, Cigdem (WILEY, 2022)
Seven novel proline and 1,2,3,4-tetrahydroisoquinoline-3-carboxylic acid (THIQA) based diamides were synthesized successfully by simple amidation reactions and characterized by their spectral data. Their catalytic activities in asymmetric aldol reaction were performed by the reactions of aliphatic ketones and various aromatic aldehydes. Especially, (S)-N-((S)-1-(morpholinoamino)-1-oxo-3-phenylpropan-2-yl)pyrrolidine-2-carboxamide (9e) showed good catalytic activities in water at room temperature in the presence of benzoic acid cocatalyst. The enantioselectivities were upto 89.6%, the diastereomeric ratios were upto 92/8, and yields were upto 97.3%. This catalyst showed its best catalytic activities in water; this is also an important contribution to green chemistry requirements.
Keywords: PROLINE-DERIVATIVES; CATALYSTS; DESIGN; Chemistry